Generation of DFMC SBAS corrections for BDS-3 satellites and improved positioning performances. Issue 3 (1st August 2020) - Zhao, Liqian; Hu, Xiaogong; Tang, Chengpan; Cao, Yueling; Zhou, Shanshi; Yang, Yufei; Liu, Li; Guo, Rui
Abstract: The next-generation satellite-based augmentation system (SBAS) will follow the dual-frequency multi-constellation (DFMC) protocol and broadcast satellite clock-ephemeris corrections and integrity information via GPS L5-like signals to improve the accuracy and integrity for GNSS dual-frequency users. BeiDou Navigation Satellite System (BDS)-3 B1C/B2a dual-frequency users will obtain a higher positioning accuracy using DFMC clock-ephemeris corrections. This paper focuses on an approach for the generation of DFMC SBAS corrections and its preliminary results. Analyzing the signal-in-space ranging error characteristics of BDS-3 satellites reveals that it is impossible to obtain orbits that are more accurate than the broadcast orbits using regionally distributed SBAS monitoring stations. Therefore, a novel DFMC SBAS correction generation approach for BDS-3 satellites is proposed in which only clock offset corrections are calculated. The effectiveness of the proposed approach is validated using measurements from mainland China. By using clock corrections only, B1C/B2a dual-frequency users can obtain the best accuracy. The results of the BDS-3 B1C/B2a dual-frequency positioning experiment show that the user equivalent ranging error is reduced from 0.59 m to 0.37 m with clock corrections but is reduced to only 0.43 m with the addition of clock-ephemeris corrections. With clock corrections only, the 95% positioning errors are reduced from 3.57 m to 1.53 m and from 3.79 m to 2.24 m in the horizontal and vertical directions, respectively, indicating a 48% reduction in positioning errors compared to users without SBAS corrections; however, the error reduction is only 40% with clock-ephemeris corrections.